ARTISTIC INTERPRETATION OF SAKKOKIY GHAZALS - Israilov, G’ayrat (FILOLOGIYA UFQLARI JURNALI, 2024)
The article is devoted to the content, ideological and artistic nature of mavlono Sakkoki’s ghazals "kim ermas ul oy mubtalosi", "yuzung khayuldurdi kushuldurdi parvona" and "gul Burun Burun qaysa qaysa çaman in işa", covering the poetic arts used in them and their interpretations of occupation. The article focused on the artistic skill of the poet, his style in praising the beauty of the garden. Feedback on the means of artistic image is given. As a result, it was found that in the gazelles of Saccocius, the suffering of sad and bereavement in love, devotion to wife and him, the enjoyment of the pleasures of life, dream is expressed in an impressive way, in a simple and melodic state. It has also been proven that in the poet’s ghazals, the aesthetic pleasure inherent in love, the high human qualities inherent in true love and Mistress are artistically expressed.